Variability in the Physiologic Response to Fluid Bolus in Pediatric Patients Following Cardiac Surgery. Issue 11 (November 2020) - Ranjit, Suchitra; Natraj, Rajeswari; Kissoon, Niranjan; Thiagarajan, Ravi; Ramakrishnan, Balakrishnan; García, M. Ignacio Monge
Abstract : Background: Fluid boluses aiming to improve the cardiac output and oxygen delivery are commonly administered in children with shock. An increased mean arterial pressure in addition to resolution of tachycardia and improved peripheral perfusion are often monitored as clinical surrogates for improvement in cardiac output. The objective of our study is to describe changes in cardiac index, mean arterial pressure, and their relationship to other indices of cardiovascular performance. Objective: The objective of our study is to describe changes in cardiac index, mean arterial pressure, and their relationship to other indices of cardiovascular performance. Design, Setting, Patients, and Interventions: We prospectively analyzed hemodynamic data from children in the cardiac ICU who received fluid bolus (10mL/kg of Ringers-Lactate over 30 min) for management of shock and/or hypoperfusion within 12h of cardiac surgery. Cardiac index responders and mean arterial pressure-responders were defined as CI ≥10% and mean arterial pressure ≥10%, respectively. We evaluated the gradient for venous-return (mean systemic filling pressure-central venous pressure), arterial load properties (systemic vascular resistance index and elastance index) and changes in vasopressor support after fluid bolus. Measurements and Main Results: Fifty-seven children between 1 month and 16 years (median Risk adjustment after congenital heart surgery Model for Outcome Surveillance in Australia and New Zealand score of 3.8 (interquartile range 3.7–4.6) received fluid bolus. Cardiac index-responsiveness and mean arterial pressure-responsiveness rates were 33% and 56%, respectively. No significant correlation was observed between changes in mean arterial pressure and cardiac index ( r = 0.035, p = 0.79). Although the mean systemic filling pressure – central venous pressure and the number of cardiac index-responders after fluid bolus were similar, the arterial load parameters did not change in mean arterial pressure-nonresponders. Forty-three patients (75%) had a change in Vasoactive-Inotrope Score after the fluid bolus, of whom 60% received higher level of vasoactive support. Conclusions: The mean arterial pressure response to fluid bolus in cardiac ICU patients was unpredictable with a poor relationship between cardiac index-responsiveness and mean arterial pressure-responsiveness. Because arterial hypotension is frequently a trigger for administering fluids and changes in blood pressure are commonly used for tracking changes in cardiac output, we suggest a cautious and individualized approach to repeat fluid bolus based solely on lack of mean arterial pressure response to the initial fluid, since the implications include decreased arterial tone even if the cardiac index increases. Abstract : Supplemental Digital Content is available in the text.